Reverse Mortgages in India: New Dimensions in Emerging Horizons - Jaishankar, P. R. (Indian Journal of Finance, 2010)
Reverse mortgage is a financial product that seeks to monetize the residential property as an asset and specifically render liquidity to the owner’s equity in the property. The product attempts to address the financial needs of house owning senior citizens. The product is generically different from a conventional mortgage product as the borrowers of a reverse mortgage do not have to make any repayment to the lender during their life time. While the product has gained significant popularity in developed nations, it had been introduced in India during May 2007. In the developed countries, the product has received significant support from the respective governments for addressing the salient risks such as longevity, property price fluctuation, legal and interest rate risks. With the increasing population of senior citizens in India, the potential for the product is enormous. Already over Rs.1400 crore have been sanctioned in its initial years of operation and over 6000 senior citizens have availed the loan. In India, the product has been introduced entirely in a market oriented manner. With a need to have sustainable, strategic and innovative financial solutions for its increasing success, a new product variant ’Reverse Mortgage Loan enabled Annuity’ has also been introduced in 2009, which offers far greater benefits to the senior citizens. This also brings about integration between the banking and insurance sectors with the housing market. The product is merely a year old and is in the process of its evolution. It is expected that measures for enhancing the attractiveness of the product would evolve in due course, thereby not only expanding the market but also the course of financial intermediation in the country.